2020
DOI: 10.1038/s41598-020-70731-6
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness status modulates the inflammatory proteins in peripheral blood and circulating monocytes: role of PPAR-gamma

Abstract: The aim of this study was to analyze the metabolic and molecular profile according to physical fitness status (Low or High VO 2max ) and its impacts on peripheral and cellular inflammatory responses in healthy men. First ( Phase I) , inflammatory profile (TNF-α, IL-6, IL-10) was analyzed at baseline and post-acute exercise sessions performed at low (< 60% VO 2max ) and high (> 90% VO 2max ) intensities considering the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 52 publications
2
18
0
Order By: Relevance
“…Genetic variations in the PPARG gene were linked to the outcome of sepsis and PPARG was suggested as a novel biomarker for sepsis [21]. The PPAR family exerts anti-inflammatory activities in immune cells, vascular smooth muscle cells, and monocytes [22]. Angiotensin II, a vasopressor used in refractory septic shock [23], inhibits PPARG activity, thereby increasing blood pressure [24].…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variations in the PPARG gene were linked to the outcome of sepsis and PPARG was suggested as a novel biomarker for sepsis [21]. The PPAR family exerts anti-inflammatory activities in immune cells, vascular smooth muscle cells, and monocytes [22]. Angiotensin II, a vasopressor used in refractory septic shock [23], inhibits PPARG activity, thereby increasing blood pressure [24].…”
Section: Discussionmentioning
confidence: 99%
“…Acetate is either directly formed from pyruvate, providing a source for acetyl-coenzyme A [ 53 ], or can be produced by the intestinal microbiota, finally entering circulation [ 54 ]. It has been suggested that a higher PF is linked to a greater abundance of gut bacteria with positive health effects, being reflected in the release of fermentation metabolites like acetate [ 55 , 56 ]. In addition to its anti-inflammatory and vasodilatory properties [ 54 ], acetate has been proposed as an important energy substrate during endurance exercise in mice [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adipocyte transcriptional activity is influenced by lifestyle factors, such as physical exercise. Early work in this field showed that exercise can upregulate the production of endogenous ligands of PPARγ, thereby increasing its transcriptional activity [ 123 ], while recent studies have shown that physical activity is associated with a direct increase in PPARγ expression [ 124 ]. The same is true for CEBP isoforms, as a strong negative correlation has been reported between exercise intensity and the expression of CEBPA and CEBPB in the obese state [ 125 ].…”
Section: Discussionmentioning
confidence: 99%